Diet of four lizards from an urban forest in an area of amazonian biome, eastern amazon - Figueiredo, Vinícius A. M. B. (2020)
This study described the diet and niche overlap of four lizards from an urban fragment in Amapá state. The samplings were performed through pitfall traps and active visual search. In the stomach analysis, Formicidae and Coleoptera represented 50.79% of the total items. The highest niche overlap value was between Gonatodes humeralis and Tropidurus hispidus, which was not expected due to habitat use. The foraging strategies of all lizards observed have been previously mentioned by several authors. Several studies cite the diet of lizards being basically composed of invertebrates, with few variations, as also demonstrated in this study.